Calorimetric Analysis of Tea and Coffee - Recep Üstünsoy; Bircan Dinç; Tahsin Ertaş (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2023)
Tea and coffee are the most popular beverage and there is a variety of forms in both hot and cold temperatures. Black tea is made from green tea leaves that have been oxidized. During the oxidation process, a certain proportion of polyphenol compounds is lost. More than a thousand chemical components can be found in coffee, making it a complex beverage. One of the significant factors that is stressed equally to the scent and flavor of coffee is the caffeine content. Differential Scanning Calorimetry (DSC) was employed in our study to compare the properties of Turkish coffee, green and black tea, and certain instant coffee brands. The evaluated teas and coffees belong to the most consumed brands in Turkey. Caffeine, which has a melting temperature of 234°C was found in abundance in green teas but not in black teas. Glass transition temperatures (Tg) for tea kinds were found to be approximately 40°C. Polyphenol content melting values are known to be approximately 67-75°C, and the study has verified that teas are high in polyphenol content. The findings of the coffee study showed that the peaks at 170 and 201°C were caused by the melting of several elements, including amino acids, lipids, and sugars, including sucrose, glucose, fructose, arabinose, galactose, maltose, and polysaccharides. Caffeine bonds are broken and degraded at temperatures of 253, 266, 278 °C, resulting in exothermic maxima. The endothermic curves at 39, 41, and 71 °C for pure coffee at three different roast levels are shown. The breakdown of the cellulose components causes the transitions to be visible between 389 and 494°C. The findings of this investigation demonstrated that instant coffees have a higher additive content than Arabica coffee.